Coal pillar mechanics of violent failure in U.S. Mines - Hamid Maleki (International Journal of Mining Science and Technology, 2017)
This paper seeks to enhance the understanding that the horizontal stresses build up and release during coal pillar loading and unloading (post-failure) drawing upon three decades of observations, geomechanical monitoring and numerical modeling in bump-prone U.S. mines. The focus is on induced horizontal stress in mine pillars and surrounding strata as highly stressed pillars punch into the roof and floor, causing shear failure and buckling of strata; under stiff stratigraphic units of some western US mines, these events could be accompanied by violent failure of pillar cores. Pillar punching eventually results in tensile stresses at the base of the pillar, facilitating transition into the post-failure regime; this transition will be nonviolent if certain conditions are met, notably the presence of interbedded mudstones with low shear strength properties and proper mine designs for controlling seismicity and dynamic loads. The study clearly shows high confining stress build-up in coal pillars resulting in up to twice higher peak vertical stress and high strain energy accumulations in some western US mines in comparison with peak stresses predicted using common empirical pillar design methods. It is the unstable release of this strain energy that can cause significant damage resulting from pillar dilation and ground movements. These forces are much greater than the capacity of most common internal support systems, resulting in horizontal stress-induced roof falls locally, in mines under unremarkable far-field horizontal stress. Attention should be placed on pillar designs as increasing support density may prove to be ineffective. This mechanism is analyzed using field measurements and generic finite-difference stress analyses. The study confirms the higher load carrying capacity of confinement-controlled coal seams in comparison with structurally controlled coal seams. Such significant differences in confining stresses are not taken into account when estimating peak pillar strength using most common empirical techniques such as those proposed by Bieniawski and Salamon. While using lower pillar strength estimates may be considered conservative, it underestimates the actual capacity of pillars in accumulating much higher stress and strain energies, misleading the designer and inadvertently diminishing mine safety. The role of induced horizontal stress in mine pillars and surrounding strata is emphasized in coal pillar mechanics of violent failure. The triggering mechanism for the violent events is sudden loss of pillar confinement due to dynamic loading resulting from failure of overlying stiff and strong strata. Evidence of such mechanism is noted in the field by observed red-dust at the coal-rock interfaces at the location of coal bumps and irregular, periodic caving in room-and-pillar mines quantified through direct pressure measurements in the gob. Keywords: Rockburst and coal bumps, Field measurements, Stress analysis, Mechanics, Horizontal stress